Rheology and Quality Research of Cereal-Based Food - Raymundo, Anabela; Torres, María Dolores; Sousa, Isabel (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
New trends in the cereal industry deal with the persistent need to develop new food goods tailored to consumer requirements and, in the near future, to the scarcity of food resources. Concepts of sustainable food production and food products as health and wellness promoters, the use of organic ingredients such as new ancient cereals to produce redesigned old staple foods, or the use of byproducts in designed food or feed formulations, in accordance with the bioeconomy and sustainability principles, are current topics that act as driving forces for innovation. The structure of cereal-based food products, especially in the case of gluten- or wheat-free foods, has proven to be a determinant for food appeal and strongly impacts consumer acceptance. It is well known that products with the same chemical composition can present very different structures, resulting in differently perceived texture and sensory properties and, therefore, rheology is an important tool for the food cereal industries. These are topics that act as driving forces for innovation and will be discussed in the present Special Issue.